Transformational leadership principles: A pathway from research to practice - Larson, J. (Olympic & Paralympic Coach, 2016)
At the 2015 National Coaching Conference in Morgantown, West Virginia, this author presented on Transformational Leadership Principles: A Pathway from Research to Practice. This article is a follow-up to that presentation. The task is to review the principles of transformational leadership as found in the current research to make application of these principles to the coaching of sport and to consider a pathway that drives research to practice. Every human endeavor will rise or fall depending on the quality of leadership. The universality of transformational leadership can be observed through a review of the current literature as extensive studies are to be found in the military, business, education, politics, religion, healthcare, and sport. There is also substantial evidence that transformational leadership is a field that can be taught and learned.